Ragam Bahasa Mahasiswa Multikultural dalam Mewujudkan Keharmonisan Komunikasi Interpersonal di Lingkungan Kampus - Wahyuni, Sri; Siti Nur Afifatul Hikmah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out the variety of multicultural student languages in realizing the harmony of interpersonal communication in the Campus Environment. This study uses a qualitative descriptive method. The data of this study was obtained from two sources, namely primary and secondary. Primary data was obtained through the stage of interviews, observations and various events of langasung speech spoken by KH University students. Mukhtar Intercession (UIMSYA). Secondary data is supported by books, references and research journals. The sample of this study consisted of four different tribes, namely: Javanese, Sundanese, Ngapak, and Ogan. The data collection technique used is to focus on the observation and interview stages. The results of this study show that UIMSYA students outside Banyuwangi who come from various regions and different tribes look confused and cannot understand the language in their new environment. The confusion was so evident when the native Banyuwangi students invited students outside Banyuwangi to communicate using Javanese, they had difficulty understanding and understanding it. So that the alternative tool used so that communication runs smoothly between the two is to use Indonesian as the official language of the Indonesian state